2023
DOI: 10.1200/op.23.00179
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Analysis of Cancer Patient Exposure, Perceptions, and Trust in Information Sources Regarding Complementary and Alternative Medicine

Ryan J. Hutten,
Christopher R. Weil,
Andy J. King
et al.

Abstract: New research from @DrHut10 and @sky__john reveals high rates of complementary and alternative medicine use in patients with cancer and characterizes trust in various sources of information regarding CAM—physicians are critically needed to combat misinformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Similar to several previous studies, 34,37 our study also showed that economic status had a significant impact on patients' TIP. Specifically, patients with higher annual incomes tended to hold lower levels of trust in their physicians.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to several previous studies, 34,37 our study also showed that economic status had a significant impact on patients' TIP. Specifically, patients with higher annual incomes tended to hold lower levels of trust in their physicians.…”
Section: Discussionsupporting
confidence: 90%